Modalities and procedures for international cooperation in competition cases involving more than one country (UN New YorkUS, 2013)
Identifies the types of cooperating models and the extent to which cooperation arrangements enhance the capabilities of competition agencies to effectively enforce competition law. Reviews the challenges in enforcing competition law at the regional and international levels and discusses how different countries have approached cooperation in the area of competition policy and its implication for improved bilateral, regional and international cooperation.
Keywords: COMPETITION